4CPS-269 Hyperthermic intraperitoneal chemotherapy associated with cytoreductive surgery in peritoneal cancer treatments: a multidisciplinary experience to evaluate its efficacy. (14th March 2021) - Rossi, F; Sturaro, C; Pieraccini, F; Ioan, P
Abstract : Background and importance: Hyperthermic intraperitoneal chemotherapy (HIPEC) associated with cytoreductive surgery (CRS) represents one of the treatments for peritoneal carcinoma of various primitivities. The treatment is effective in terms of disease free interval and survival. From January 2019 to June 2019, 33 HIPEC associated with CRS were performed under the supervision of a team of oncologists, surgeons and pharmacists. Aim and objectives: The aim of the work was to describe the management of HIPEC and CRS in an Italian hospital and the response of patients to treatment. Material and methods: At the time of surgery, 33 patients had an average peritoneal cancer index of 14.9. Complete cytoreduction was achieved in 29 patients. The drugs used during HIPEC were for: carcinosis with colic primitivity (42.5%): oxaliplatin, fluorouracil, leucovorin in one case; cisplatin, mitomycin in eight cases; mitomycin in three cases; carcinosis with gastric primitivity (21.2%): in six cases cisplatin, mitomycin; in one case cisplatin, paclitaxel; carcinosis with ovarian primitivity (21.2%): in five cases cisplatin, paclitaxel; in two cases cisplatin, doxorubicin; LAMN (9.0%), cisplatin and mitomycin; cholangiocarcinoma (3%), cisplatin, mitomycin; mesothelioma (3%), cisplatin, doxorubicin. The average age of the patients was 55.8 years and 63.6% were women. Results: Mean ICU stay was 6.7 days, while the mean total hospital stay was 21.8 days. Inhospital mortality was 12%. The complication rate during hospitalisation (CTCAE ≥2) was 33.3%. Four patients (12%) underwent reoperation. Of the 29 patients discharged from hospital, 8 patients (27.6%) relapsed and, among them, 2 patients (6.9%) died. The mean OS calculated from the Kaplan–Meier curves of the discharged patients was 9.4 months and the mean DFS was 7.4 months. To date, the patients analysed have a survival rate of 81.8% (27 of the 33 patients are alive to date) and a DFS of 71.4% (20 of the 28 patients are currently free from illness). Conclusion and relevance: Considering the positive results obtained so far, the study of HIPEC with CRS in peritoneal carcinoma continues, to evaluate its effectiveness. The role of the pharmacist was important in participating in the multidisciplinary team in terms of eligibility of patients for treatment, to prepare oncological therapies and in processing the evaluation data. References and/or acknowledgements: Conflict of interest: No conflict of interest